WTO, agriculture, and developing countries: a survey of issues - Díaz-Bonilla, Eugenio; Robinson, Sherman; Thomas, Marcelle; Yanoma, Yukitsugu (International Food Policy Research Institute, 2002)
The objective of this paper is to present a survey of trade issues in agriculture from the perspective of developing countries. Developing countries are a large percentage of the World Trade Organization (WTO) membership, and agriculture is critical for their economic growth, poverty alleviation, food security, and environmental sustainability. First, this paper identifies trends in production, consumption, and trade of food and agriculture over the last decades. Some of the significant developments include the emergence of oilseeds and fruits and vegetables as the main exports from developing countries, replacing traditional exports such as sugar, coffee and cocoa. The trends also show a worsening of developing countries’ net trade position due in part to income growth and population pressures, but also to economic policies in general, and trade policies in particular, both in developing and industrialized countries. Second, this paper focuses on some of the main development issues linked to the WTO agricultural negotiations. The objective is to align the different legal components and subcomponents of the negotiations under the Agreement on Agriculture, with developing countries’ final objectives of sustainable economic growth, poverty alleviation, and food security. This paper concludes that the problems for developing countries are not legal constraints under the AoA, but the lack of financial and human resources and institutional capabilities. To link negotiations to their development goals, developing countries must consider the issue of funding. Finally, developing countries, most of which have embarked in unilateral liberalization over the last decade, should ask that the higher levels of protection in industrialized countries be reduced first.